Elagolix reduced dyspareunia and improved health-related quality of life in premenopausal women with endometriosis-associated pain. Issue 4 (December 2019) - Leyland, Nicholas; Taylor, Hugh S; Archer, David F; Peloso, Paul M; Soliman, Ahmed M; Palac, Hannah L; Martinez, Marisol; Abrao, Mauricio S
Objectives: The objective was to evaluate the effects of elagolix on dyspareunia in women with endometriosis-associated pain. Methods: Data were pooled from two similar, randomized, double-blind, placebo-controlled, 6-month phase 3 studies (Elaris Endometriosis-I and Elaris Endometriosis-II) of elagolix at two doses (150 mg QD and 200 mg BID) in women with endometriosis-associated pain. In this post hoc analysis, dyspareunia responders were defined as having a clinically meaningful decrease from baseline in the dyspareunia score and decreased or stable use of rescue analgesic agents, as recorded in a daily electronic diary. Sexual relationship was assessed using the 30-item Endometriosis Health Profile questionnaire sexual relationship module. Results: A total of 1384 women reported ⩾1 day of sexual activity at baseline (35 days prior to and including day 1 of treatment). Of these 1384 women, 1297 (94%) reported ⩾1 day of any dyspareunia (mild, moderate, or severe), of which 51% reported ⩾1 day of severe dyspareunia. Among sexually active women who reported any dyspareunia at baseline, both elagolix doses led to improvements in dyspareunia. Women in the 200-mg BID group showed more months at which the dyspareunia response rates were statistically significantly greater than placebo, particularly in a subgroup of women with severe dyspareunia at baseline. Compared to placebo, both elagolix doses led to statistically significantly greater improvements in the mean 30-item Endometriosis Health Profile sexual relationship module score. Conclusion: Up to 6 months of elagolix treatment improved dyspareunia in women with endometriosis-associated pain in a dose-dependent manner, with 200-mg BID dose showing the most significant improvements in dyspareunia and quality of sexual relationships compared with placebo.